THE DEVELOPMENT OF A MONOPOLY GAME TO IMPROVE ARABIC VOCABULARY MASTERY AMONG 7TH-GRADE STUDENTS OF SMP ISLAM PLUS DAARUL ARQAM - Indriati, Sukma; Herni, Zulfiana (Universitas Islam Negeri Sumatera Utara Medan, 2025)
This study was motivated by the low mastery of Arabic vocabulary among seventh-grade students of SMP Islam Plus Daarul Arqam due to learning that was still monotonous and teacher-centered. This condition indicates the need for an innovative, engaging, and interactive learning medium. The research focused on developing an Arabic Monopoly game as a learning medium, assessing its feasibility, and testing its effectiveness in improving vocabulary mastery. The objective of the study was to produce a feasible and effective learning medium. The method used was Research and Development (R&D) with the 4D model, consisting of the stages of Define, Design, Development, and Disseminate. The results showed that the developed medium was highly feasible, with a media expert validation score of 97.5% and a material expert score of 93.75%, as well as a teacher response of 88.89%. The effectiveness of the medium was demonstrated by an improvement in learning outcomes from pre-test to post-test of 98.07%, with an N-gain value of 0.9808 categorized as high. Therefore, the Monopoly game is effective in improving students’ mastery of Arabic vocabulary.